Swiss Dairy Farmers' Perceptions Surrounding the Disposal of Waste Milk Containing Antibiotic Residues and Antibiotic Resistance - Bernier Gosselin, Véronique; Visschers, Vivianne H. M.; Bodmer, Michèle; Meylan, Mireille (Frontiers in Veterinary Science, 2022)
The feeding of waste milk containing antibiotic residues (WMA) to calves has been associated with the shedding of antibiotic-resistant bacteria by calves. However, little is known regarding farmers' intrinsic factors affecting this practice, and on which it would be relevant to intervene in order to change this practice. The objectives of this study were 1) to describe the farmers' intrinsic factors, such as perceived benefits, risks, and social norms related to the feeding of WMA to calves, antibiotic resistance, and antibiotic use, and 2) to evaluate how the feeding of WMA to calves is related to farmers' personal values and perceptions related to WMA feeding and antibiotic resistance. Answers to an online survey were collected from 233 Swiss dairy producers (38.3% response rate). The proportion of respondents who fed WMA to calves was 48.3%. In a hierarchical logistic regression model, only perception factors extracted by factor analysis were associated with the feeding of WMA to calves, namely (in decreasing order of magnitude): farm-level benefits of WMA feeding, the interaction of farm-level benefits with support from governmental authorities, and causes and threats of antibiotic resistance. The results suggest that, in order to reduce the feeding of WMA to calves, communications to dairy producers should focus on changing the perceived benefits of this practice in comparison to those of alternative WMA disposal methods carrying a lower risk of AR. The involvement of veterinarians and governmental authorities in these communications and in supporting producers may increase the successful adoption of alternative WMA disposal methods.